Periodontal Status of the Adjacent Second Molar after Impacted Mandibular Third Molar Surgical Extraction - Pham, Thuy Anh Vu (Contemp Clin Dent, 2019)
OBJECTIVE: The purpose of this study was to evaluate the change in periodontal status of the adjacent second molar of the impacted mandibular third molar after surgical extraction and its association with the third molar condition in the presurgical stages, including position, eruption level, and local complications. MATERIALS AND METHODS: The study was based on a 6-month follow-up of 38 patients (19 males and 19 females; Mean age: 21.89 ± 2.74) recruited consecutively after surgical extraction of an impacted lower third molar. The third molar's presurgical position, eruption level, and local complications were examined. Periodontal status, including Plaque Index (PI), Gingival Index (GI), and gingival bleeding on probing (BOP), of the teeth in the adjacent sextant was clinically evaluated. The pocket depth (PD) and the distance between the epithelial attachment and the adjacent second molar's occlusal surface were clinically measured; and the distance between the alveolar bone crest and cementoenamel junction (AC–CEJ) of the adjacent second molar was evaluated by the periapical film. All measures were recorded at the time of surgery and 1, 3, and 6 months after surgery. RESULTS: The values of PI, GI, BOP, PD, and EA–OS were significantly reduced after 1, 3, and 6 months compared to baseline data. The AC–CEJ was decreased after 1 month but significantly increased after 3 and 6 months. Presurgical local complications of the impacted third molar mostly were significantly associated with the periodontal status of the adjacent sextant. CONCLUSION: There was a significant improvement of periodontal conditions of the second molar and adjacent sextant after impacted third molar surgery.